Markups, markdowns, and bargaining in a vertical supply chain - Rémi Avignon; Claire Chambolle; Etienne Guigue; Hugo Molina G. (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This article bridges monopoly, monopsony, and countervailing power theories to analyze their welfare implications in a vertical supply chain. We develop a bilateral monopoly model with bargaining that accommodates upstream monopsony and downstream monopoly power. In equilibrium, the ''short-side rule'' applies: the quantity exchanged is determined by the firm willing to trade less. Welfare is maximized when each firm's bargaining power exactly countervails the other's market power. Otherwise, double marginalization arises in the form of double markdownization under excessive downstream bargaining power, or double markupization under excessive upstream bargaining power. We offer novel insights for price regulation (e.g., price floors) and competition policy.
Keywords: C78; D42; J42; 330; markups; markdowns; bargaining; countervailing buyer power; monopsony power; bilateral monopoly